2016
DOI: 10.1021/acs.jafc.6b00361
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of ‘Gold Finger’ Grape Berry Quality as Affected by the Different Rootstocks

Abstract: Berry qualities of the grafted 'Gold Finger' grapevines were determined to evaluate the impacts of the resistant rootstocks on fruit quality. Compared to the own-rooted vines, berry and cluster weights and skin color were altered by the rootstocks to varying extents. The rootstock of 101-14M maintained TSS/TA and the contents of fructose, glucose, and sucrose, and SO4 decreased these parameters. 101-14M and 3309C increased and reduced the resveratrol content, respectively. SO4, 5BB, and 3309C decreased the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 33 publications
2
19
1
Order By: Relevance
“…Content of sugars and acids greatly determines the organoleptic quality of grapes and the ratio of sugars to titratable acids is commonly used to evaluate fruit maturity [ 24 ]. In the present study, Fe deficiency and excess lead to poor wine grape quality, decreased RS content and increased TAC, and hence the lower RS/TAC ratio.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Content of sugars and acids greatly determines the organoleptic quality of grapes and the ratio of sugars to titratable acids is commonly used to evaluate fruit maturity [ 24 ]. In the present study, Fe deficiency and excess lead to poor wine grape quality, decreased RS content and increased TAC, and hence the lower RS/TAC ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The genes investigated in this study are key genes in the flavonoid pathway, which are usually used in related studies [ 17 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Phenylalanine ammonia-lyase (PAL) is a key enzyme for phenylpropanoid metabolism, it may indirectly related to anthocyanin biosynthesis [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the nitrogen capability of grapevines plays an important role in vine growth, which is closely related to grape composition, as described above. Several studies have indicated that grape compositions may be regulated by rootstocks through affecting the concentrations of amino acids in grape berries [7,9,19,20]. Jogaiah et al [7] showed that the accumulation of sugar may be affected by rootstocks through regulating the ratio of arginine to proline in berries.…”
Section: Introductionmentioning
confidence: 99%
“…At the molecular level, even though the molecular mechanism underlying the interaction between rootstock and scion remains unclear, several researchers have revealed that rootstocks can mediate scions through the modification of hormones; the regulation of gene expression; and the large-scale movement of proteins, mRNAs, and small RNAs [21]. Jin et al [20] revealed that the expression of genes related to sugar, amino acids, and flavonoid metabolism in ‘Gold Finger’ berries was largely modified by rootstocks.…”
Section: Introductionmentioning
confidence: 99%